Ethnoscience Study of the Application and Delivery Procession of Adat Melayu Jambi as Science Learning Resources - Irma Fadilah; Rizki Intan Sari; Vega Ramadhani; Fibrika Rahmat Basuki; Olva Fitaloka (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2019)
This research aims to reconstruct and analyze the concept of science in the application and delivery procession of Adat Melayu Jambi. This study used a qualitative approach through ethnoscience studies, a study of knowledge systems organized from existing cultures in society. The subjects of this study ware customary leaders and science education experts. Data were collected through in-depth interviews, observations, and documentation. The data were analyzed descriptively by using Miles and Huberman analysis model. Test the validity of the data with triangulation. The procession of the application and customary delivery is part of the traditional procession of Jambi Malay wedding procession. The procession starts from the introduction (berusik sirih berguraupinang), applying (tegak batuik duduk betanyo), and custom delivery (ulur antar serah terimo adat dan lembago). In the procession of the application and the customary distribution, the groom usually takes a series of souvenirs (Tepak Sirih/Kepalo Baso) (containing betel, betel lime, gambier, areca nut, tobacco), rattan split ring, graduated clothes and giving â€œadatâ€ (gold, gold scales, selarih rifles, and spears) and â€œlembagoâ€ (buffalo, 100 ropes coconut, â€œselemak semanis seasam segaram,